Efektivitas Model Pembelajaran Motorik Berbasis Movement Based Games Pada Siswa Sekolah Dasar - Riesca Andrian; Suroto Suroto; Abdul Rachman Syam Tuasikal; Sigra Santika Satria Dhani; Setyorini Setyorini (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2020)
This article is conducted in order to provide an alternative learning model that can be chosen by the teacher to learn fundamental movement skills in elementary school. The learning model which is described in this article is the result of research and development using Borg and Gall model. This article focuses on discussing the effectiveness of applying the learning model by using MBG on health sport and physical education learning. The effectiveness was measured by testing the MBG model to 70 students on fourth grade. The effectiveness measurement was carried out on the quality of the process by using the Formative Class Evaluation (FCE) questionnaire while the quality of the results used the fundamental movement skills measurement instrument. Data analysis was conducted by using descriptive statistics and different tests used t-test based on the results of the normality test data distribution by using Kolmogorov-Smirnov. The results showed that the quality of the learning process was included in the good category. On the other hand, learning outcomes before and after learning showed a significant increase (p <0.05). Hence, it can be concluded that the MBG development result model is effectively applied in health sport and physical education learning, especially in fourth grade.